Pulau Perambut, an islet of goethite off Kedah, and its signficance - Lee, M.C. (Malaysian Journal of Science, 1999)
Pulau Perambut, an islet near the eastern end of Pulau Bunting off Kedah, is all goethite, which represents a lode trending 030. The goethite is derived from magnetite that had been earlier oxidised to hematite. The goethite is niobian and is believed to be owed to its occurrence in a region of columbite mineralisation. The occurrence of magnetite veins associated with quartz porphyry intrusions is suggested to be another possibility for the occurrence of the magnetic anomaly on the coast opposite Pulau Bunting,